2020
DOI: 10.21203/rs.3.rs-19784/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative analysis of macrophage activation in the synovium of healthy and osteoarthritic equine joints

Abstract: Background: Synovitis is a major component of osteoarthritis and is driven primarily by macrophages. Synovial macrophages are crucial keepers of joint health by driving joint homeostasis, tissue repair and inflammation resolution (M2-like phenotype), but can also induce an inflammatory response (M1-like phenotype) when these regulatory functions are overwhelmed. Macrophage phenotypes in synovium from osteoarthritic and healthy joints are poorly characterized. Defining the patterns of synovial macrophage pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…BMNCs consists of a population of ~50% naïve macrophages and approximately 25% of hematopoietic progenitors polarized towards the M2 subtype; this favors healing, apparently through the production of IL-10, and results in clinical improvement. It has also been suggested that some of the anti-inflammatory effects of MSCs can be attributed to precocious myeloid differentiation at the expense of self-renewal due to chronic inflammatory stimuli, as they do not produce high quantities of IL-10 themselves [ 26 , 40 , 89 , 90 , 91 ].…”
Section: Immunomodulatory Therapies In Equine Practicementioning
confidence: 99%
“…BMNCs consists of a population of ~50% naïve macrophages and approximately 25% of hematopoietic progenitors polarized towards the M2 subtype; this favors healing, apparently through the production of IL-10, and results in clinical improvement. It has also been suggested that some of the anti-inflammatory effects of MSCs can be attributed to precocious myeloid differentiation at the expense of self-renewal due to chronic inflammatory stimuli, as they do not produce high quantities of IL-10 themselves [ 26 , 40 , 89 , 90 , 91 ].…”
Section: Immunomodulatory Therapies In Equine Practicementioning
confidence: 99%